Drop dead healthy : one man's humble quest for bodily perfection - Jacobs, A. J., 1968- (New York : Simon & Schuster, 2012)
"Having sanctified himself in The Year of Living Biblically and sharpened his mind in The Know-It-All, A. J. Jacobs had one feat left in the self-improvement trinity: to become the healthiest man in the world. He didn't want just to lose weight, or finish a triathlon, or lower his cholesterol. His ambitions were far, far greater : Maximal health from head to toe.The task was massive. He had to tackle a complicated web of diet and exercise advice, much of which was nonsensical, unproven, and contradictory. He had to consult a team of medical advisers. And he had to subject himself to a grueling regimen of exercises, a range of diets, and an array of practices to improve everything from his hearing to his sleep to his sex life all the while testing the patience of his long-suffering wife. He left nothing untested, from the caveman workout to veganism, from the treadmill desk to extreme chewing. Drop Dead Healthy teems with hilarity and warmth and pushes our cultures assumptions about and obsessions with what makes good health, allowing the reader to reflect on his or her own health, body, and eventual mortality"--Provided by publisher.
Includes index.
Keywords: Jacobs, A. J., -- 1968- -- Health; Health; Nutrition -- Biography; Exercise; Health -- Humor